Assessing the Impact of Data Sciences and Smart Technologies in Air Conditioning Project Management: A Delphi Method Analysis within the Construction Industry - Ali, Bashar Mahmood; Akkaş, Mehmet (MDPI AG, 2023)
The integration of data sciences and smart technologies in the construction industry, particularly in air conditioning project management, is an important area of research. This study employs the Delphi Method to explore this integration, surveying 40 experts in construction management. Participants were meticulously selected based on a set of inclusion criteria related to age, educational qualifications, and field experience. The study tests five hypotheses, each scrutinized through a score-based Delphi analysis. The findings are mixed and shed new light on several dimensions of air conditioning project management. For instance, the study refutes the commonly held belief that the location of air conditioning projects significantly impacts worker safety. It also challenges the assumption that exceeding international safety standards like ISO leads to cost savings. On the other hand, the study validates the significance of global safety standards and the undeniable role of data sciences and smart technologies in enhancing human safety in the air conditioning industry. These findings not only challenge existing models, but also open avenues for further research. They indicate a complex interplay between safety, cost-effectiveness, and technological integration in air conditioning project management. The study suggests a shift towards data-driven decision-making and underscores the need for international safety standards, particularly in an era marked by rapid technological advancements and globalization.
Keywords: intelligent data analyzing; Building construction; thermal comfort; energy consumption; Delphi method; air conditioning; building business; TH1-9745; 9. Industry and infrastructure